Seed dressing with M451 promotes seedling growth in wheat and reduces root phytopathogenic fungi without affecting endophytes - Kardava, K.; Tetz, V.; Vecherkovskaya, M.; Tetz, G. (Frontiers in Plant Science, 2023)
Fungal plant infections result in substantial losses to the agricultural sector. A range of fungicide seed dressings are available to control seed-borne fungal diseases; however, they lack sufficient efficacy because of intrinsic tolerance and acquired resistance. Moreover, many fungicide seed dressings can also penetrate plants, negatively affecting plant growth owing to their toxic effects on endophytes, as well as contributing to the spread of antibiotic resistance. Here, we evaluated the efficacy of M451, a member of a new class of antimicrobial agents that are not relevant to human healthcare. As a seed dressing for wheat seeds, M451 exhibited significant antifungal activity against one of the most devastating plant fungal pathogens, Fusarium spp. Furthermore, M451 was more active than the commercially used fungicide Maxim XL against both seed-borne and soil-borne F. oxysporum infection. Importantly, and unlike other antifungals, M451 seed dressing did not inhibit any of the major characteristics of wheat grains and seedlings, such as germination percentage, germination time, grain vigor, shoot- and root weight and length, but rather improved some of these parameters. The results also demonstrated that M451 had no negative impacts on endophytes and did not accumulate in grains. Thus, M451 may have potential applications as an antifungal agent in wheat cultivation.